2001
DOI: 10.4049/jimmunol.166.3.1590
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Human Cord Blood CD34+ Cell-Derived NK Cell Cytotoxicity by Dendritic Cells

Abstract: NK cells and dendritic cells (DCs) are both important in the innate host defense. However, the role of DCs in NK cell-mediated cytotoxicity is unclear. In this study, we designed two culture systems in which human cord blood CD34+ cells from the same donor were induced to generate NK cells and DCs, respectively. Coculture of the NK cells with DCs resulted in significant enhancement of NK cell cytotoxicity and IFN-γ production. However, NK cell cytotoxicity and IFN-γ production were not increased when NK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
107
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 66 publications
4
107
0
1
Order By: Relevance
“…In addition, DCs have been reported to activate NK cells by secretion of cytokines (IL-12 and IL-18) and costimulatory molecules. 45,46 Because NK cells can kill cancer cells that show low MHC class I expression, the activation of not only CTLs but also NK cells is helpful in melanoma therapy. These cytotoxic cells are stimulated in the lymph nodes by antigen presentation and/or cytokine secretion of mature DCs that migrate after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DCs have been reported to activate NK cells by secretion of cytokines (IL-12 and IL-18) and costimulatory molecules. 45,46 Because NK cells can kill cancer cells that show low MHC class I expression, the activation of not only CTLs but also NK cells is helpful in melanoma therapy. These cytotoxic cells are stimulated in the lymph nodes by antigen presentation and/or cytokine secretion of mature DCs that migrate after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…DC-NK cross-talk through cytokines has been recently confirmed with human DC and NK cells derived in vitro from cord blood CD34 ϩ cells [34]. In this case an involvement of IL-12, IL-18, and possibly IFN-␥ produced by DC was unraveled, showing also a possible role of DC-expressed CD40 acting through an unknown counterreceptor on NK cells distinct from CD40L [34]. In both pieces of work, DC were matured with TNF-␣ prior to exposure to NK cells.…”
Section: Discussionmentioning
confidence: 83%
“…It is worth mentioning in this regard that functionally inducible membrane-associated IL-12 on DC has been reported [50]. DC-NK cross-talk through cytokines has been recently confirmed with human DC and NK cells derived in vitro from cord blood CD34 ϩ cells [34]. In this case an involvement of IL-12, IL-18, and possibly IFN-␥ produced by DC was unraveled, showing also a possible role of DC-expressed CD40 acting through an unknown counterreceptor on NK cells distinct from CD40L [34].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…With the recent development of culture methods for propagating DC on a large scale from human peripheral blood mononuclear cells (PBMC) (Caux et al, 1992;Sallusto and Lanzavecchia, 1994), vaccination aimed at efficient production of CTL with tumour-antigenloaded DC represents a potentially powerful strategy to induce tumour rejection (Young and Inaba, 1996;Nestle et al, 1998). Moreover, since it has also been reported that DC stimulate NK cell activity (Fernandez et al, 1999;Yu et al, 2001), DC should be considered to be associated intimately with not only the production of CTL but also with the whole process of antitumour cellmediated immunity. However, there is little published information regarding the influence of cimetidine on DC function.…”
mentioning
confidence: 99%